the Normative Legal Views in Handling Electronic Dispute Resolution Abroad through International Arbitration Legal Entities - Regi Kinaryosi; Ikhsan Harahap; Dafa Alfarizi; Indra Naposo Harahap (ISNU Sumatera Utara, 2024)
The rapid growth of e-commerce has transformed international trade by enabling cross-border transactions without requiring direct interaction between business actors and consumers. Despite its advantages, e-commerce also increases the risk of cross-border commercial disputes, particularly regarding defective products, contractual breaches, and compensation claims. Conventional litigation is often considered inefficient due to differences in legal systems, jurisdiction, and enforcement mechanisms among countries. Consequently, international arbitration, particularly electronic arbitration, has emerged as an effective alternative dispute resolution mechanism. This study aims to analyze the legal framework governing electronic arbitration in Indonesia and examine the enforceability of international online arbitral awards under Indonesian law. The research employs a normative juridical method using statutory and conceptual approaches. Legal materials were obtained through library research and analyzed qualitatively using a deductive method. The findings indicate that Indonesian law recognizes electronic arbitration through Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution, Law Number 11 of 2008 as amended by Law Number 19 of 2016 on Electronic Information and Transactions, and the Indonesian National Arbitration Board (BANI) Electronic Arbitration Rules. Electronic arbitration provides a faster, more efficient, and confidential dispute resolution process while maintaining procedural fairness. However, the enforcement of international arbitral awards in Indonesia remains subject to several legal requirements, including the principle of reciprocity, commercial subject matter, compliance with Indonesian public policy, and the issuance of an exequatur by the Central Jakarta District Court. Therefore, although electronic arbitration offers significant advantages for resolving cross-border e-commerce disputes, further harmonization of legal regulations is necessary to strengthen legal certainty and improve the effectiveness of enforcing international arbitral awards in Indonesia.